2019
DOI: 10.5430/rwe.v10n2p20
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Multi Dimensional EO in the Competitive Strategy - Performance Link

Abstract: Despite the increase market in catering industry by 37% per year, the number of SME-catering service firms is only 30.000, or only 5% from the total number of SME in 2016. From 30,000 registered catering service company, only 10% is an active business with annual growth rate (3%). In order to achieve competitive advantage and growth, firms will develop appropriate competitive strategy, strategy which directly relate to firm performance. The purpose of this paper is to develop a better understanding of the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Indeed, Wong et al (2016) demonstrated the positive relationship between competitive advantage and the operational performance of Malaysian firms. Basbeth et al (2019) also showed the relationship between competitive advantage and firm performance in the context of Jakarta's small and medium-sized catering services. However, Kharub et al (2019) could not prove a direct relationship between low-cost advantage and firm performance.…”
Section: 7mentioning
confidence: 98%
“…Indeed, Wong et al (2016) demonstrated the positive relationship between competitive advantage and the operational performance of Malaysian firms. Basbeth et al (2019) also showed the relationship between competitive advantage and firm performance in the context of Jakarta's small and medium-sized catering services. However, Kharub et al (2019) could not prove a direct relationship between low-cost advantage and firm performance.…”
Section: 7mentioning
confidence: 98%
“…Thanks to the technological capabilities and differentiation strategy of a technologically oriented company, it improves product quality, adds features and value, and increases product performance, thus competitive advantage (Porter, 1985). Basbeth et al (2009) found that individual entrepreneurship orientation has a moderator role in the relationship between differentiation strategy and firm performance, as well as cost leadership strategy and firm performance. With a different approach, it has been found that competitive strategies have a moderator effect in the relationship between entrepreneurial orientation and firm performance -cost leadership has a negative effect, and differentiation strategy has a positive effect (Galbreath et al, 2020).…”
Section: The Relationship Between Generic Competition Strategies and ...mentioning
confidence: 99%
“…In other related perspectives, Baba (2015) postulates the strategic orientation as the organization's philosophy of how to conduct business which reflecting enhanced values with its environment. The principles are related process in which business and social organization engage with offering new products or new services, risk taking, innovation, and pro-active action in their activities and business process (Basbeth et al, 2019;Miller, 1983). Strategic orientation guides the direction of the social organization to pursue their activities (Storey and Hughes, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Strategic orientation (SO) is gaining more attention in determining the performance and competitive advantage of many organizations (Aloulou, 2019). Strategic oriented organization normally embarked with strategic principles of market orientation, technology orientation or entrepreneurial orientation that influence organization activities and behaviours that intended to gain best performance (Basbeth et al, 2019;Chatzoglou et al, 2018). SO substantially influences organization activities, investments and their economic performance by mobilizing their valuable assets, capabilities, technology and skills (Al-Ansaari, Bedder & Chen, 2015;Gamba, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation